Electrospun phospholipid nanofibers encapsulated with cinnamaldehyde/HP-β-CD inclusion complex as a novel food packaging material. (June 2021) - Li, Changzhu; Chen, Wenqing; Siva, Subramanian; Cui, Haiying; Lin, Lin
Highlights: HP-β-CD was utilized to enhance the water solubility and thermal stability of CA. CA/HP-β-CD phospholipid nanofibers as novel food packaging material were developed. CA/HP-β-CD inclusion complex was embedded into phospholipid nanofibers. A regulated release of cinnamaldehyde has been achieved by CA/HP-β-CD inclusion complex. CA/HP-β-CD nanofibers had high antibacterial activity against Listeria monocytogenes . Abstract: To develop a novel food packaging material, hydroxypropyl-β-cyclodextrin (HP-β-CD) with good water solubility was used to encapsulate cinnamaldehyde (CA). The prepared CA/HP-β-CD inclusion complex (CA/HP-β-CD-IC) was further embedded into the nanofibers, which were composed of phospholipid and poly (ethylene oxide). FTIR and molecular structure modeling indicated that CA was encapsulated in HP-β-CD most probably by directly inserting the phenyl of CA into the cavity of HP-β-CD. Subsequently, the preferable mechanical properties with the uniform diameter distribution of the mat of nanofibers were realized. Meanwhile, the thermal stability of CA was further improved after being embedded into HP-β-CD and the mat of nanofibers. For the application on fresh-cut cucumber, the mat of nanofibers encapsulated with CA/HP-β-CD-IC exhibited antibacterial activity against Listeria monocytogenes at 4 °C and 25 °C for 4 days, without significant effect on the sensory indicators of fresh-cut cucumber. Thus, the mat of nanofibers encapsulated with CA/HP-β-CD-IC could be a promising and practical food packaging material.